Use of Indirect Evidence in Disclosure of Cartel Violations According To Business Competition Law in Indonesia - WIGANARTO, Tri Utomo; GULTOM, Elisatris; PERMANA, Sudaryat (Indonesia Strategic Sustainability, 2024)
In cartel evidence, there are two approaches, namely direct evidence and indirect evidence . The Law on Monopolistic Practices and Unfair Business Competition in Indonesia does not yet regulate the use of indirect evidence as evidence to prove the occurrence of a cartel . The ambiguity of this regulation causes legal uncertainty in the use of indirect evidence in the decision of the Business Competition Supervisory Commission (KPPU). This study discusses the use of indirect evidence in disclosing cartel violations according to the Business Competition Law in Indonesia by harmonizing the ideal concept and studying the relevant laws and regulations. The method of normative juridical approach. The research specification is descriptive analysis. Data was collected by using Library Research and analyzed using qualitative juridical . The results of the study indicate that there is an ambiguity in the arrangement of indirect evidence in the case of business competition in Indonesia, namely cartels. Although further regulation has been regulated in KPPU Regulation Number 1 of 2019 concerning Procedures for Handling Cases of Monopolistic Practices and Unfair Business Competition, this has not yet been regulated at the level of law.